Able or disabled - (:unkn) unknown (Emerald Publishing Limited, 2024)
Purpose: This paper aims to answer the question: To what extent should neurodiverse students experience improved access to public universities in Egypt and why? Design/methodology/approach: A systematic qualitative research method was used with data coll...
Keywords: Discapacidad; Inclusión